AN ERRORS ANALYSIS IN TRANSFORMING ACTIVE TO PASIVE FORM OF INDRAPRASTA PGRI STUDENTS (VISUAL COMMUNICATION DESIGN PROGRAMME) - Fitria Iswari (Journal of English Language Teaching and Literature (JELTL), 2020)
Universitas indraprasta PGRI , students get the English subject in first year, and one of material is passive voice form. From the students score in examination, the result is they had low score in transforming active to passive form. From that condition the writer do a research of an errors analysis in transforming Active to Passive form. The purpose of the research is to find the errors of students in transforming active to passive form. This is descriptive qualitative research which the data collection is gotten from test and interview. The data shows there are 428 errors in transforming active to passive voice from 4 classes randomly. From the data analysis, it can be taken a conclusion that students did all types of errors (omission, addition, misformation, misordering) . From 4 classes there are 428 errors that they had made. And the highest errors are omission which is 134 errors, and the lowest errors are misformation which is 83 Errors. Misordering is 91 errors and addition is 120 errors. From the interview the writer got that students do not know the tenses of active voice so they cannot change rightly to passive voice.